2021
DOI: 10.1002/capr.12481
|View full text |Cite
|
Sign up to set email alerts
|

Cultural humility in psychotherapy and clinical supervision: A research review

Abstract: When Tervalon and Murray-Garcia (1998), both renowned physicians, educators and activists (e.g., melanietervalon.com), first introduced the term, cultural humility, into the literature approximately 25 years ago (Tervalon & Murray-Garcia, 1998), they may well not have realised how impactful and far reaching their new concept would become. What was then new has now become a vital and integral part of a general ethic and culture of care (Foronda, 2020;Hook et al., 2017), increasingly recognised by, and practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 41 publications
(70 reference statements)
3
38
0
Order By: Relevance
“…Future research may seek to explicate other discursive strategies, linked to other CH‐related dimensions. Relatedly, as CH may change over time, context, and relational dyad (Zhang et al., 2021), we encourage broad consideration of the range of possibilities to assess the frequency and proportional use of the identified discursive strategies throughout counselor training and practice. Another possible direction is to develop an observer‐rated scale of CH‐linked discursive strategies to complement the existing CH measures, all of which rely exclusively on self‐report data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research may seek to explicate other discursive strategies, linked to other CH‐related dimensions. Relatedly, as CH may change over time, context, and relational dyad (Zhang et al., 2021), we encourage broad consideration of the range of possibilities to assess the frequency and proportional use of the identified discursive strategies throughout counselor training and practice. Another possible direction is to develop an observer‐rated scale of CH‐linked discursive strategies to complement the existing CH measures, all of which rely exclusively on self‐report data.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, there has been growing empirical evidence supporting the role of CH in counseling and supervision (Kondili et al., 2022; Watkins et al., 2019; Zhang et al., 2021; Zhu et al., 2021). In a seminal study, Hook et al.…”
Section: Introductionmentioning
confidence: 99%
“…This must be done within an environment of cultural humility in which both parties are willing to reflect on oneself as a cultural being with related limitations and both are willing to understand the other's cultural identities and experiences (Watkins et al, 2019). Research suggests that cultural humility strengthens the supervisory alliance and is related to increased supervisory outcomes (Zhang et al, 2021). The authors of this article maintain that it is critical that mutual understandings of worldviews, biases, and performance expectations are established at the outset of the evaluative relationship and before feedback, an outcome of supervision, is provided.…”
Section: The Context Of Evaluation In Healthmentioning
confidence: 99%
“…In reviews of studies examining multicultural orientation, therapists’ missed cultural opportunities and lower cultural comfort have been associated with less symptom improvement and earlier termination among clients (Davis et al, 2018). Furthermore, therapist cultural humility has been positively associated with treatment outcomes and ratings of therapeutic alliance (Zhang et al, 2022). Similarly, in a meta-analysis of 15 studies, Tao et al (2015) found that client ratings of multicultural competence are associated with higher ratings of processes such as treatment satisfaction and therapeutic alliance and greater symptom improvement.…”
Section: Importance Of Therapist Attunement To Client Disclosures Of ...mentioning
confidence: 99%